Autotaxin inhibitors: A patent review - Barbayianni, E.; Magrioti, V.; Moutevelis-Minakakis, P.; Kokotos, G. (Expert Opinion on Therapeutic Patents, 2013)
Introduction: Autotaxin (ATX) is a lysophospholipase D enzyme that hydrolyzes lysophosphatidylcholine to lysophosphatidic acid (LPA) and choline. LPA is a bioactive lipid mediator that activates several transduction pathways, and is involved in migration, proliferation and survival of various cells. Thus, ATX is an attractive medicinal target. Areas covered: The aim of this review is to summarize ATX inhibitors, reported in patents from 2006 up to now, describing their discovery and biological evaluation. Expert opinion: ATX has been implicated in various pathological conditions, such as cancer, chronic inflammation, neuropathic pain, fibrotic diseases, etc. Although there is an intensive effort on the discovery of potent and selective ATX inhibitors in order to identify novel medicinal agents, up to now, no ATX inhibitor has reached clinical trials. However, the use of ATX inhibitors seems an attractive strategy for the development of novel medicinal agents, for example anticancer therapeutics.